2011
DOI: 10.3354/meps09189
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of salt marsh creeks and ditches as habitat for nekton

Abstract: Salt marshes are dynamic systems supporting a diverse assemblage of resident and transient nekton (free-swimming fish and decapod crustaceans). Within a marsh, many sub-habitats are used by nekton, including ditches and natural creeks. While the use of natural creeks is well documented, the role of ditches as habitat for nekton remains less well known. The present study describes the nekton-support function of this prolific marsh sub-habitat, and compares it to tidal creeks. Sampling was conducted in the summe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Greater isolation of ponds may mean their fish populations cannot be restocked if the ponds dry out or some other ecological catastrophe strikes. Knieb (1997) suggested all artificial aquatic habitats in marshes have natural functional analogs, and ditches act like tidal channels; however, Corman and Roman (2011) disagree, as their data showed distinct water quality differences. A comprehensive report on fish in marshes did not find any special role for ditches as habitat (Rountree and Able 2007).…”
Section: Fish and Other Nektonmentioning
confidence: 95%
See 3 more Smart Citations
“…Greater isolation of ponds may mean their fish populations cannot be restocked if the ponds dry out or some other ecological catastrophe strikes. Knieb (1997) suggested all artificial aquatic habitats in marshes have natural functional analogs, and ditches act like tidal channels; however, Corman and Roman (2011) disagree, as their data showed distinct water quality differences. A comprehensive report on fish in marshes did not find any special role for ditches as habitat (Rountree and Able 2007).…”
Section: Fish and Other Nektonmentioning
confidence: 95%
“…One Long Island study found shallow ditches in a microtidal marsh (which had poor water quality) did not support as many fishes and species as creeks did (Corman and Roman 2011). When ditches were converted to ponds and more natural appearing channels in another Long Island marsh, there were significant increases in overall nekton populations (Rochlin et al 2012).…”
Section: Fish and Other Nektonmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, the ditches act as additional tidal channels, thereby sometimes (but not always) reducing ponding on the marsh platform, which is a critical foraging habitat for a subset of marsh birds (Burger et al 1982, Erwin 1996, Trocki and Paton 2006. These habitat and hydrologic changes can not only affect birds, but also invertebrates and fishes at multiple levels of the marsh food web, thereby indirectly impacting birds at higher trophic levels (Bourn and Cottam 1950, Dreyer and Niering 1995, Corman and Roman 2011. Consequently, there is the potential for the marsh bird community to exhibit complex responses to ditching.…”
Section: Introductionmentioning
confidence: 99%